The disciple - Coonts, Stephen, 1946- (St. Martin's Press, 2009)
Iran is weeks away from acquiring nuclear weapons and has every intention of using them to strike first-- only Tommy Carmellini and Jake Grafton can stop a nuclear nightmare.